Pengaruh Karakteristik Perusahaan dan Good Corporate Governance Terhadap Pengungkapan Corporate Social Responsibility - Sutra Dewi; Heri Yanto (Jurnal Akuntansi Bisnis, 2021)
The purpose of this study is to examine the effect of company characteristics (profitability, leverage, company size) and GCG (board size, proportion of independent commissioners, managerial ownership) on CSR disclosure. The population in this study was the mining sector companies listed on the IDX from 2017 to 2019, amounting to 47 companies. Purposive sampling was used in the study, and data were collected by utilizing documentary approaches, obtaining a final sample of 69 analysis units. The data analysis technique used was descriptive statistical and inferential statistical analysis with the IBM SPSS 25 application. The result shows that profitability, leverage, the proportion of independent commissioners, and managerial ownership significantly negatively affect CSR disclosure, but company size has a significant positive effect on CSR disclosure. in contrast, the board size does not affect CSR disclosure. This study concludes that the bigger the company size, the higher the CSR disclosure. Furthermore, the higher the profitability, leverage, proportion of independent commissioners, and managerial ownership, the lower the CSR disclosure.